Evaluation of knowledge Intensive Care anesthesia technicians In Prevention of Ventilator Associated Pneumonia in Libyan public Hospitals - Fahima Albashir Albeshti; Ghada Mohammed Algeblaw; Amal Alesabri; Alaa Swiss; Ali Elfandiy (African Journal of Advanced Pure and Applied Sciences, 2025)
Background: Ventilator-associated pneumonia (VAP) is a common hospitals- acquired infection occurs in patients requiring treatment in intensive care units (ICUs) it affects between 6–52% of the cases requiring the use of berating ventilators in hospitals, resulting in hospital length of stay (LOS) of more than 48 hours. This increases morbidity, mortality, and healthcare cost Aim: to evaluate the knowledge and performance of anesthesia technicians in preventing Ventilator-associated pneumonia in intensive care unit ICU. Method: The study was descriptive, data were collected from100 technicians anesthesia working in Zawia and Al Khadra public Hospital in Tripoli in intensive care, to assess their knowledge Ventilator-associated pneumonia, in relation to their sociodemographic characteristics, qualification level and years of experience, starting from March to May 2024. It was based on proved multiple- choice questionnaires developed to assess ICU medical knowledge about the evidence based guidelines for the prevention of VAP using (ANOVA test) Results: In this study ICU technicians displayed generally good understanding of Ventilator-associated pneumonia prevention, with an average knowledge score of (0.76 ± 0.12) out of 18 questions. And the 57% of technicians showed good knowledge, while 43% showed inadequate knowledge. Also, Marital status was also demographic factor significantly associated with knowledge scores, with married technicians showing better knowledge than single ones. Conclusion: Although some anesthesia technicians showed good performance in preventing (VAP) in the ICU. This study recommended many educational and training programs to improve the knowledge level of anesthesia technicians in ICUs.